Atividade antimicrobiana da BthTx-I e seu uso como melhorador de desempenho alternativo na avicultura - Silveira, Ana Carolina Portella (2013)
The purpose of this study was to evaluate the antimicrobial activity of venoms of Bothrops alternatus, Bothrops jararaca, Bothrops pauloensis, Bothrops jararacussu, Bothrops moojeni, and Crotalus durrissus terrificus of the Viperidae family of Gram-positive Staphylococcus aureus and Enterococcus faecalis and Gram-negative Escherichia coli and Salmonella enteritidis. The aim was to identify the fraction of venom showing activity. The Mueller-Hinton Agar disc-diffusion and broth microdilution methods were used according to standard techniques. The B. jararacussu venom showed the bests results, and Bothropstoxin-I (BthTx-I), a Lys49 phospholipase A2 from this venom, was chosen for evaluation as an alternative performance growth factor using broilers and microbiological, biochemical, and histological parameters. We used 84 broilers aged 21 and 28 days divided into three feed treatments; one diet included bacitracin zinc (positive control), a second had the addition of BthTx-I, and a third contained no additives (negative control). Bacterial counts of litters and cloacal swabs of broilers were tested; BthTx-I was found to decrease the microbial population in cloacal swabs in relation to other groups without altering body weight or the chemical composition of carcasses or causing changes in serum biochemistry, intestinal morphology, and histopathology of livers and kidneys of animals. Thus, BthTx-I could act at the intestinal level, reducing the microbial load of potentially pathogenic bacteria without causing muscle, liver, and kidney lesions in broilers.